Surface Enhanced Raman Spectroscopy 2010
DOI: 10.1002/9783527632756.ch9
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical SERS and its Application in Analytical, Biophysical and Life Science

Abstract: Raman spectroscopy, as a vibrational spectroscopy, can record fingerprint spectra from electrodes and provide much insight into a variety of surface and interfacial processes at the molecular level: for example, qualitatively determining surface bonding, conformation and orientation. Raman spectroscopy invariably uses lasers from the ultraviolet (UV) to the near infrared (NIR). More importantly, the technique can be applied in situ to investigate solid-liquid, solid-gas and solid-solid interfaces of both funda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Raman spectroelectrochemistry [14][15][16][17] (TR-Raman SEC) is used to follow the roughening process of silver with a Raman probe molecule in the electrolytic solution, being possible to detect transient processes [18][19][20]. Thus, SERS SEC system allows both, the electrochemical investigation and also the simultaneous SERS data, and therefore presents wide applicability in target molecules analysis with low detection limit.…”
Section: Introductionmentioning
confidence: 99%
“…Raman spectroelectrochemistry [14][15][16][17] (TR-Raman SEC) is used to follow the roughening process of silver with a Raman probe molecule in the electrolytic solution, being possible to detect transient processes [18][19][20]. Thus, SERS SEC system allows both, the electrochemical investigation and also the simultaneous SERS data, and therefore presents wide applicability in target molecules analysis with low detection limit.…”
Section: Introductionmentioning
confidence: 99%
“…Simply considering |E| 4 , a maximum enhancement E max for a single molecule adsorbed on an isolated Ag nanoparticle is not larger than 10 8 , whereas the EM enhancement for a nanoparticle dimer can be up to ~10 11 . This enhancement is comparable with the necessary precondition for observing an SMR event although this estimation has ignored charge transfer, possible resonance effect and long‐range coupling effect from the nanoparticle aggregations . If considering all these contributions, a total enhancement factor for SMR could be up to ~10 14 .…”
Section: Single‐molecule Ramanmentioning
confidence: 78%
“…On optimized substrates, a concentration limitation up to ~10 −15 or ~10 −16 M has been attained for SMR observation of certain analytes . Moreover, it was indicated that metal electrode systems could also support SMR events, but concentration limit is a challenge …”
Section: Single‐molecule Ramanmentioning
confidence: 99%